GC-MS SCREENING, ACUTE TOXICITY AND IN VIVO ANTIDIABETIC ACTIVITY OF THE METHANOL WHOLE PLANT EXTRACT OF Plantago rugelii (Plantaginaceae) - Ogbiko, Cyril (FUDMA JOURNAL OF SCIENCES, 2021)
A metabolic disorder like Diabetes Mellitus requires serious attention to prevent its associated long-term complications. Plantago rugelii is an important medicinal plant used in South-South Nigeria for the management and treatment of diabetes mellitus amongst others. The present investigation focuses on the GC-MS profile, oral acute toxicity and the antidiabetic potential of the methanol whole plant extract of the plant. The fresh whole plant was obtained,air-dried, pulverized, cold macerated using absolute methanol and concentrated to dryness. Acute oral toxicity was conducted using standard procedure. The oral antidiabetic effect was evaluated in vivo on six groups of rats with five rats per group. Diabetes was induced by a single intraperitoneal injection of alloxan monohydrate (160 mg/kg) in ice-cold 0.9% v/v normal saline. The extracts at 50, 100 and 200 mg/kg body weight reduced glycaemia by 30.43%, 43.78% and 59.54% respectively as against the glibenclamide treated rats, which has an 82.77% reduction. There was no mortality at 4 g/kg p.o. after 24 hours and no sign of delayed toxicity or mortality after 14 days of observation. The GC-MS spectra revealed twenty-one (21) phytoconstituents of which some have established antidiabetic effects. The antidiabetic effect of the plant could be attributed to the presence of the established biological phytochemicals however; bioassay-guided isolation and characterization of the phytocompound(s) should be carried out to identify the lead compound(s).
Keywords: Plantago rugelii, GC-MS, diabetes, antidiabetic, toxicity